Performance of Granulated Ti-Dopped Manganese Oxide Oxygen Carriers in Chemical Looping Processes - Teresa Mendiara; Amirhossein Filsouf; Iñaki Adánez-Rubio; María Teresa Izquierdo; Alberto Abad (Applied Sciences)
The cornerstone in the development of different applications of the Chemical Looping (CL) technology is the oxygen carrier material that transfers the oxygen. We evaluate the performance of manganese oxide doped with TiO2 to reinforce the release of molecular oxygen and regeneration at high temperatures (850–950 °C). Different manganese-titanium mixed oxides with mass fractions of titanium oxide from 0 to 50 wt.% were considered and prepared by granulation. The sample with 20 wt.%. TiO2 (MnTi_20) showed better oxygen release/regeneration capabilities than pure manganese oxide under similar conditions and was selected for further development. To evaluate the performance of MnTi_20, long tests (200 cycles) were carried out in a TGA to evaluate the chemical and mechanical stability of the sample. Additionally, MnTi_20 was tested in a batch fluidized bed reactor to evaluate its oxygen uncoupling capability and its reactivity with the main combustion gases (H2, CO, and CH4) as well as its fluidization properties. MnTi_20 is capable of regenerating Mn3O4 to Mn2O3 at 950 °C and maintains its reactivity with the redox cycles. No fluidization problems were encountered during almost 60 h of continuous fluidization, and a lifetime of 2500 h was estimated for this oxygen carrier.